High performance dental resin composites with hydrolytically stable monomers. Issue 2 (February 2018) - Wang, Xiaohong; Huyang, George; Palagummi, Sri Vikram; Liu, Xiaohui; Skrtic, Drago; Beauchamp, Carlos; Bowen, Rafael; Sun, Jirun
Graphical abstract: Highlights: High performance, hydrolytically stable dental resin composites. Composition-controlled photo-polymerization. Significantly reduced polymerization stress and improved materials' strength and toughness. Chemical and mechanical stability under clinically-relevant conditions. Dentin-matching aesthetics. Abstract: Objective: The objectives of this project were to: 1) develop strong and durable dental resin composites by employing new monomers that are hydrolytically stable, and 2) demonstrate that resin composites based on these monomers perform superiorly to the traditional bisphenol A glycidyl dimethacrylate/triethylene glycol dimethacrylate (Bis-GMA/TEGDMA) composites under testing conditions relevant to clinical applications. Methods: New resins comprising hydrolytically stable, ether-based monomer, i.e., triethylene glycol divinylbenzyl ether (TEG-DVBE), and urethane dimethacrylate (UDMA) were produced via composition-controlled photo-polymerization. Their composites contained 67.5 wt% of micro and 7.5 wt% of nano-sized filler. The performances of both copolymers and composites were evaluated by a battery of clinically-relevant assessments: degree of vinyl conversion (DC: FTIR and NIR spectroscopy); refractive index ( n : optical microscopy); elastic modulus ( E ), flexural strength ( F ) and fracture toughness ( KIC ) (universal mechanical testing); Knoop hardness ( HK ; indentation); water sorption ( Wsp ) and solubility ( Wsu ) (gravimetry); polymerization shrinkage ( Sv ; mercury dilatometry) and polymerization stress (tensometer). The experimental UDMA/TEG-DVBE composites were compared with the Bis-GMA/TEGDMA composites containing the identical filler contents, and with the commercial micro hybrid flowable composite. Results: UDMA/TEG-DBVE composites exhibited n, E, Wsp, Wsu and Sv equivalent to the controls. They outperformed the controls with respect to F (up to 26.8% increase), KIC (up to 27.7% increase), modulus recovery upon water sorption (full recovery vs. 91.9% recovery), and stress formation (up to 52.7% reduction). In addition, new composites showed up to 27.7% increase in attainable DC compared to the traditional composites. Bis-GMA/TEGDMA controls exceeded the experimental composites with respect to only one property, the composite hardness. Significantly, up to 18.1% lower HK values in the experimental series (0.458 GPa) were still above the clinically required threshold of approx. 0.4 GPa. Significance: Hydrolytic stability, composition-controlled polymerization and the overall enhancement in clinically-relevant properties of the new resin composites make them viable candidates to replace traditional resin composites as a new generation of strong and durable dental restoratives.